Challenge Level

Ho Chung gives a solution here:

For the first two equations, the answer is the cube root of 3, by observation. You can simply substitute this value in the equation and verify that it is a solution. We have to show that these are the only possible solutions.

What follows is really an argument by contradiction. If we assume that there exists a solution less than the cube root of 3 we reach an impossible situation and likewise for one greater than the cube root of 3.

Define a sequence $(x_n)$ by $x_1=x^3$, $x_{n+1}=x^{x_n}$. Observe that for $x> 1$, if $x^3> 3$ then the sequence is strictly increasing, and if $x^3< 3$ then the sequence is strictly decreasing.

Now to solve $x^{(x^3)}=3$, we are imposing $x_2=3$, so the sequence becomes $x^3$, 3, $x^3, 3, ...$. Since we must have $x> 1$ and the sequence is neither strictly increasing nor strictly decreasing, we must have $x^3=3$. This also clearly works. So $x=\sqrt[3]{3}$.

Similarly, to solve $x^{(x^{(x^3)})}=3$, we have $x_3=3$, so the sequence becomes $x^3$,$x^{(x^3)}$, 3, $x^3, ... $ and so again we have $x=\sqrt[3]{3}$.

For the general equation $$x^{x^{x^{x^{x^{x^{...^{n}}}}}}}=n$$ where the sequence of powers is defined in the same way, and $n$ is a positive integer, we can use the same argument. The solution is the $n$-th root of $n$ if $n$ is odd and when $n$ is even there are two solutions $x=\pm n^{1/n}$.

For the first two equations, the answer is the cube root of 3, by observation. You can simply substitute this value in the equation and verify that it is a solution. We have to show that these are the only possible solutions.

What follows is really an argument by contradiction. If we assume that there exists a solution less than the cube root of 3 we reach an impossible situation and likewise for one greater than the cube root of 3.

Define a sequence $(x_n)$ by $x_1=x^3$, $x_{n+1}=x^{x_n}$. Observe that for $x> 1$, if $x^3> 3$ then the sequence is strictly increasing, and if $x^3< 3$ then the sequence is strictly decreasing.

Now to solve $x^{(x^3)}=3$, we are imposing $x_2=3$, so the sequence becomes $x^3$, 3, $x^3, 3, ...$. Since we must have $x> 1$ and the sequence is neither strictly increasing nor strictly decreasing, we must have $x^3=3$. This also clearly works. So $x=\sqrt[3]{3}$.

Similarly, to solve $x^{(x^{(x^3)})}=3$, we have $x_3=3$, so the sequence becomes $x^3$,$x^{(x^3)}$, 3, $x^3, ... $ and so again we have $x=\sqrt[3]{3}$.

For the general equation $$x^{x^{x^{x^{x^{x^{...^{n}}}}}}}=n$$ where the sequence of powers is defined in the same way, and $n$ is a positive integer, we can use the same argument. The solution is the $n$-th root of $n$ if $n$ is odd and when $n$ is even there are two solutions $x=\pm n^{1/n}$.